GENERAL INTERACTION BETWEEN LANGUAGE, GESTURE AND TRANSLATION - Absamatova Gulkhayo Bakhodirovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. In this article we want to pay special attention to gestures since we encounter them all the time, both on the street and at work, and in our free time. The gestures with which we illustrate our speech either help or hinder listeners from perceiving information. They say a lot about us as speakers. They make a significant contribution to the result of our performance.